Cowpea bean β-vignin-derived AQQSY peptide exerts an anticancer effect by inducing cell cycle arrest in the G0/G1 phase and modulating apoptotic signals - Biane Oliveira Philadelpho; Johnnie Elton Machado dos Santos; Emily Elaine Davis; Mariana Barros de Cerqueira e Silva; Eduardo Maffud Cilli; Ederlan de Souza Ferreira; Elvira González de Mejia (Journal of Functional Foods)
The anticancer effect of digested β-vignin and pure peptides from cowpea beans was investigated in cultivated human colon cancer cells. The effect of AQQSY on the cell cycle was similar to that of palbociclib, suggesting that AQQSY may function as a CDK-6-targeting agent. AQQSY peptide reduced the p-Rb/Rb ratio and induced apoptosis through an increase of Bax/Bcl-2 ratio, a decrease of XIAP, and activation of caspase-3. VIPASY peptide showed the potential to induce apoptosis through an increase in Bax/Bcl-2 ratio. The combination of VIPASY and AQQSY with palbociclib caused an additive effect on cell inhibition. Treatment with selected peptides from β-vignin digest caused cell cycle arrest by upregulation of p16 and apoptosis by increasing Bax/Bcl-2 ratio and caspase-8. The peptides and β-vignin digest treatments were more selective for cancer cells than the drugs. Additional research is necessary in vivo to understand the mechanisms of cowpea β-vignin-derived peptides in CRC treatment.